Chinese Overseas Foreign Direct Investment and the Sino-Serbian Strategic Partnership. (1st July 2014) - Graham Hollinshead
Abstract : While considerable scholarly attention has been devoted to foreign direct investment into China, the emergent status of the People's Republic as an outward investor of growing international significance has, arguably, been subject to neglect. Yet 'going overseas' has been a fundamental element in the reform and modernisation of the Chinese economy, this policy having been formally ratified by the Chinese Communist Party in the late 1990s, with China having now ascended to the position of third most important investor abroad, after the USA and Japan. Scrutiny of the particular nature of Chinese overseas foreign direct investment (OFDI) is instructive because it reveals that, while its determinants may be familiar from a Western perspective, peculiarities are also evident, notably an integral involvement of the state in its inception. As the global spread of Chinese OFDI has now extended to Europe, this paper examines the particular case of the Sino-Serbian strategic partnership, a major element of which relates to Chinese assistance in the reconstruction of the Serbian infrastructure. This paper focuses on a Chinese-sponsored construction project on the edge of Europe. It first considers the flows and specific determinants of Chinese OFDI. The geopolitical connotations of China's economic interventions overseas are then highlighted. Finally, it offers an exposition of the Sino-Serbian strategic partnership and the Chinese-sponsored 'Bridge of Friendship' currently being constructed over the River Danube near Belgrade. The paper concludes that aspects of Chinese OFDI are powerfully conditioned by underlying geo-political and foreign policy objectives prevalent in the home country as well as economic considerations.